2019
DOI: 10.1093/nsr/nwz124
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution mapping of brain vasculature and its impairment in the hippocampus of Alzheimer's disease mice

Abstract: Accumulating evidence indicates the critical importance of cerebrovascular dysfunction in the pathogenesis of Alzheimer's disease (AD). However, systematic comparative studies on the precise brain vasculature of wild-type and AD model mice are still rare. Using an image-optimization method for analysing Micro-Optical Sectioning Tomography (MOST) data, we generated cross-scale whole-brain 3D atlases that cover the entire vascular system from large vessels down to smallest capillaries at submicron resolution, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
68
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(75 citation statements)
references
References 57 publications
7
68
0
Order By: Relevance
“…This distribution is similar to the mean radius measured in other serial sectioning modalities e.g. MOST (49) and for clearing techniques (50) although no large vessels (>10 μm) are present in MF-HREM data, due to the preferential binding of lectin to microvasculature over larger vessels as noted previously (50).…”
Section: Resultssupporting
confidence: 88%
“…This distribution is similar to the mean radius measured in other serial sectioning modalities e.g. MOST (49) and for clearing techniques (50) although no large vessels (>10 μm) are present in MF-HREM data, due to the preferential binding of lectin to microvasculature over larger vessels as noted previously (50).…”
Section: Resultssupporting
confidence: 88%
“…In AD mouse models, live cortex imaging through a cranial window, or reconstructing the hippocampal vasculature of fixed brains, also showed a reduction of mean capillary diameter compared to normal mice [ 55 , 133 , 193 ], which in cortex reflected capillary constriction near pericyte somata [ 133 ]. Nortley et al [ 133 ] further demonstrated that, in the AD model mouse they used, neither arterioles nor venules had an altered diameter, implying that the reduction of CBF is generated by capillaries (although this still remains to be shown for human AD and other AD mouse models).…”
Section: Cerebral Blood Flow Decreases In Ad Largely Reflect Pericytementioning
confidence: 99%
“…It remains unclear why the capillary thrombosis is mainly located in the cortex, instead of the striatum and hippocampus. It has been documented that the topological distribution of the capillary network is different throughout the brain to match the regional metabolism ( Shaw et al, 2019 ; Zhang et al, 2019 ). The vascular network shows distinct distribution and density in the cortex, hippocampus and striatum.…”
Section: Discussionmentioning
confidence: 99%
“…The cortical parenchyma is full of abundant vessels, which are well arranged into a mesh-like network. The vascular density in the hippocampus is significantly lower than the cortical vessel density ( Zhang et al, 2019 ). No obvious difference of vascular density is seen between the striatum and cortex ( Di Giovanna et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%